To Study The Effect of Intrathecal Dexmedetomidine As An Adjuvant To Isobaric Ropivacaine 0.75% In Lower Abdominal Surgeries - Reddy, Swathi; Taksande, Karuna; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Background and aim: This study will be conducted to study the efficacy of intrathecal dexmedetomidine as an adjuvant to 0.75% isobaric ropivacaine in various lower abdomen surgeries. Objective is to evaluate the initiation and the duration of the sensory block and motor block along with various hemodynamic parameters and postop analgesia. Methodology in this study is sixty patients will be divided into two groups of 30each. The group R will be receiving three ml of isobaric ropivacaine 0.75% and 0.1 ml of NS via intrathecal route and group RD will be receiving three ml of isobaric ropivacaine 0.75% and dexmedetomidine 10mcg intrathecally in lower abdominal surgeries. Results: it is anticipated that the onset of block and duration of the sensory block and motor block, prolongs the postoperative analgesia and also will maintain the haemodynamic stability. It will also show that side effects will be less with addition of dexmedetomidine as an adjuvant. Conclusion: dexmedetomidine added as an adjuvant to isobaric ropivacaine intrathecally is superior to ropivacaine alone.